Design of 8-shaped Trajectory Carbon-free Car based on Cylindrical Cam Driving - Jiao Fei; Chen Lihang; Dai Menglian; Li Xu; Yao Lei (Jixie chuandong)
According to the requirements of the Fifth National College Students ’ Comprehensive Ability Competition in Engineering Training,the design and production of cam structure based on the 8-shaped carbon-free car is completed. According to the theoretical trajectory of the carbon-free car,the design and parameter calculation of the transmission mechanism and the steering mechanism of the car are carried out. The kinematic equation of the car is obtained,and the motion trajectory of the car is simulated according to Motion analysis in Solid Works. Parameters such as cylindrical cam are optimized. The test results show that the carbon-free car can complete 11 times 8-shaped tracing movement,which archived the purpose of walking according to the intended track and verified the rationality of the mechanism.